Alkali metals doped cycloparaphenylene nanohoops: Promising nonlinear optical materials with enhanced performance - Ruqiya Rasul; Tariq Mahmood; Khurshid Ayub; Khurram Saleem Joya; Farooq Anwar; Nazamid Saari; R. Nawaz; Mazhar Amjad Gilani (Heliyon, 2023)
In the ongoing pursuit of novel and efficient NLO materials, the potential of alkali metal-doped {6}cycloparaphenylene ({6}CPP) and methylene bridged {6} cycloparaphenylene (MB{6}CPP) nanohoops as excellent NLO candidates has been explored. The geometric, electronic, linear, and nonlinear optical properties of designed systems have been investigated theoretically. All the nanohoops demonstrated thermodynamic stability, with remarkable interaction energies reaching up to −1.39 eV (−0.0511 au). Notably, the introduction of alkali metals led to a significant reduction in the HOMO-LUMO energy gaps, with values as low as 2.92 eV, compared to 6.80 eV and 6.06 eV for undoped {6}CPP and MB{6}CPP, respectively. Moreover, the alkali metal-doped nanohoops exhibited exceptional NLO response, with the K@r6-{6}CPP complex achieving the highest first hyperpolarizability of 56,221.7 × 10−30 esu. Additionally, the frequency-dependent first hyperpolarizability values are also computed at two commonly used wavelengths of 1550 nm and 1907 nm, respectively. These findings highlight the potential of designed nanohoops as promising candidates for advanced NLO materials with high-tech applications.